Monitoring of ambient air PCDD/F levels in Portugal - Coutinho, Miguel (2007)
As part of a monitoring program conducted by IDAD – Institute for Environment and Development and supported by regional municipal solid waste (MSW) management authorities, dioxin concentrations in ambient air were measured in three regions of Portugal: Porto, Lisbon and Madeira. These independent studies were performed with the intention of providing data as a basis for the evaluation of potential impacts of the operation of recently built MSW incinerators. Thus, 170 samples were collected in nine different sites from January 1999 till present. The measured levels revealed an extremely variable content of PCDDs/PCDFs depending both on the area and the season of the year. Samples taken in Porto and Lisbon reveal a similar homologue structure even if concentrations measured in the Porto region are significantly greater. Data from Madeira is characteristic of a remote site with some of the congeners concentrations below the detection limit.